A New Porous Metallic Carbon Allotrope with Interlocking Pentagons for Sodium‐Ion Battery Anode Material. Issue 6 (25th April 2021) - Ni, Dongyuan; Guo, Yaguang; Shen, Yupeng; Wang, Qian
Abstract: The high rate performance of metal‐ion batteries requires the anode to be conductive not just ionically but also electronically. This criterion has significantly stimulated study on porous metallic carbon with intrinsically high electron conductivity. In contrast to the previously reported metallic T6‐carbon constructed by interlocking carbon hexagons, here a new 3D metallic carbon composed of interlocking carbon pentagons, penta‐h22, is proposed. Based on state‐of‐the‐art theoretical calculations, it is shown that penta‐h22 is energetically more stable than T6‐carbon. More importantly, different from T6‐carbon with too small pores for metal ions, penta‐h22 possesses a large specific capacity of 609 mAh g –1, low diffusion barrier of 0.20 eV, low open‐circuit voltage of 0.63 V, and small volume change of 1.75%. These parameters clearly indicate that pentagon‐based 3D porous carbon is promising for the anode of Na‐ion batteries. Abstract : A new 3D metallic carbon allotrope, penta‐h22, composed of trifoliate‐pentagonal carbon units, exhibits a high specific capacity of 609 mAh g −1, a low energy barrier of 0.20 eV for Na‐ion diffusion, low open‐circuit voltage of 0.63 V, and a small volume change of 1.75% during charging and discharging, showing promise for sodium‐ion battery anode.